Maternal body composition in relation to twinning - Thomas Nilsen; Per Magnus; Ragnhild Ørstavik (Norsk Forening for Epidemiologi, 2016)
Monozygotic (MZ) twinning is considered to be a random event whereas spontaneous dizygotic (DZ) twinning is influenced by several factors. Thus, secular changes in twinning rates are usually explained by changes in DZ twinning alone. Maternal body mass index (BMI) before pregnancy and maternal height are believed to be significant drivers of twinning. Our aim in this study was to explore to what degree maternal body composition influences twinning. Data on births and maternal height and BMI from the Medical Birth Registry Norway (MBRN) was analyzed applying multivariate logistic regression analysis. The results showed that increasing maternal BMI and height has a positive association with twinning. There is an increased risk of DZ twinning for a maternal BMI > 25, OR 1.31-1.43 and for maternal height ≥ 173 cm, OR 1.28. In explaining secula